Effects of cassava waste substitution for maize in weaner rabbit diets (1996)
The maize in a weaner rabbit diet was substituted with cassava waste meal (CWM) at 0,25,50, 75 and 100%. The effects of these treatments on the performance, nutrient digestibility and haematology of the rabbits were evaluated in a 70-day feeding trail period. Twenty-five littermate New Zealand white rabbits between 6 -7 weeks old averaging 750 ±25.23g were used. The rabbits were randomly alloted to five treatments and each animal was individually accommodated in metal cages. Feed and water were provided ad libitum. The mean voluntary feed intake increased (P < 0.05) with increasing levels of cassava waste meal inclusion in the diets. The body weight gain decreased (P <0.05) along the dietary treatments. The lowest average daily weight gain was recorded in rabbits fed 100% cassava waste meal inclusion, while the feed efficiency decreased (P < 0.05) correspondingly with increasing levels of CWM in the diets. Except for crude ash which were similar (P > 0.05), apparent digestibility for the other dietary components were different (P < 0.05) among treatments. The haematological values were unaffected (P > 0.05). This study indicates that CWM can replace up to 75% of maize in rabbit diets without compromising growth and digestibility.